Optimalisasi Manajemen Keuangan dalam Menstabilkan Perekonomian Keluarga di Desa Temaji Kecamatan Jenu - Istiqomah, Nur Hidayatul; M. Rizky Fauzi; Siswoyo Siswoyo; Inarotul A’yun; Dian Rustyawati; Diana Nur Indah P; Supriyanto Supriyanto; Widya Istiqomah; Ahmad Aryansyah (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2025)
The challenges in family financial management, such as expenditures exceeding income, lack of savings, and reliance on consumer debt, have become major issues for the community of Desa Temaji, Jenu District. This community service program aims to enhance the understanding and skills of families, especially mothers, in financial management to achieve economic stability. The methods used include an initial study, interactive training, and pre- and post-training knowledge evaluation. The results of the training show a significant improvement in participants' ability to create budgets, manage debt, and prioritize needs. The implementation of the financial strategies taught has enabled families to manage their income more wisely, build emergency funds, and reduce dependence on debt. The success of this program demonstrates that a systematic approach focused on local needs can be an effective solution in improving family economic stability.